Evaluating Vendors’ Level of Usage towards Paleng-QR PH Plus in Public Mall in Ozamiz City - Maglinte, John Marv D.; Maluto, Stefanie Grace O.; Tenorio, Kevin B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The growing demand for convenient and secure financial transactions has increased the relevance of cashless payment systems in the country. The Paleng-QR PH Plus program, initiated by the Bangko Sentral ng Pilipinas (BSP) and the Department of the Interior and Local Government (DILG), aims to promote digital payment usage in public markets and local transportation. Grounded with the Technology Acceptance Model (TAM), understanding how individuals accept and use technology, this study aims to assess vendors' level of usage and identify the challenges encountered in using the system. A concurrent mixed-methods research design was employed to obtain both numerical data and personal insights for a deeper understanding of the vendors' experiences. A total of one hundred ninety (190) vendors participated in the survey, while twenty (20) vendors were interviewed. Results revealed that among the six (6) variables, three (3) had very high implications, while the other three (3) were rated high. However, 'habit' ranked the lowest, indicating vendors have not fully integrated digital payments into daily transactions. Four major challenges were also identified: one (1) frequent application updates, two (2) slow public Wi- Fi connection, three (3) cellular load requirements, and four (4) lack of digital literacy. Based on the findings, the respondents suggested the need for targeted training programs to improve digital literacy, continuous education on using digital payments, and technical support to build vendor confidence. Thus, structured training and support mechanisms must be implemented to encourage regular usage and ensure long-term adoption of the digital payment system.